QUALITY OF LIFE OF PATIENTS WITH DIABETES MELLITUS - Normatov Murodjon Buribayevich; Yarmatov Suvon Tatlibayevich (Scholar Express Journals, 2023)
The problem of quality of life (QOL) in diabetes mellitus (DM) worries scientists all over the world. DM is a severe somatic disease, the treatment of which requires strict adherence to a diet, regular intake of hypoglycemic and corrective drugs, mandatory medical supervision. It has been proved that the nonparticipation of the DM patient in the treatment leads to psychological depression, withdrawal into the disease, prevents the conduct of a full-fledged lifestyle, contributing to the social maladaptation of patients. First of all, with DM, such aspects of QOL suffer as: psychological, professional, family, social and financial, as well as physical, mental and sexual.A number of studies have been devoted to the problems of psychosocial maladaptation of patients with DM. 21% of young patients have difficulties in school related to the disease. Problems in obtaining the desired job are noted in 28% of patients; 19% of patients lost their jobs, 41% of patients encountered the problem of changing their place of work. The conflict zone for women with DM is violations of intrafamily relations, and for men - industrial relations.
Keywords: Quality of life; diabetes mellitus; hypoglycemic